Population pharmacokinetic study of benzathine penicillin G administration in Indigenous children and young adults with rheumatic heart disease in the Northern Territory, Australia. (13th July 2022) - Kado, Joseph; Salman, Sam; Hand, Robert; O'Brien, Margaret; Ralph, Anna; Bowen, Asha C; Page-Sharp, Madhu; Batty, Kevin T; Dolman, Veronica; Francis, Joshua R; Carapetis, Jonathan; Manning, Laurens
Abstract: Background: Benzathine penicillin G (BPG) is the cornerstone of secondary prophylaxis to prevent Streptococcus pyogenes infections, which precede acute rheumatic fever (ARF). The paucity of pharmacokinetic (PK) data from children and adolescents from populations at the highest risk of ARF and rheumatic heart disease (RHD) poses a challenge for determining the optimal dosing and frequency of injections and undermines efforts to develop improved regimens. Methods: We conducted a 6 month longitudinal PK study of young people receiving BPG for secondary prophylaxis. Throat and skin swabs were collected for microbiological culture along with dried blood spot (DBS) samples for penicillin concentrations. DBSs were assayed using LC-MS/MS. Penicillin concentration datasets were analysed using non-linear mixed-effects modelling and simulations performed using published BMI-for-age and weight-for-age data. Results: Nineteen participants provided 75 throat swabs, 3 skin swabs and 216 penicillin samples. Throat cultures grew group C and G Streptococcus . Despite no participant maintaining penicillin concentration >20 ng/mL between doses, there were no S. pyogenes throat infections and no ARF. The median (range) observed durations >20 ng/mL for the low- and high-BMI groups were 14.5 (11.0–24.25) and 15.0 (7.5–18.25) days, respectively. Conclusions: Few patients at highest risk of ARF/RHD receiving BPG for secondary prophylaxis maintain penicillin concentrations above the target of 20 ng/mL beyond 2 weeks during each monthly dosing interval. These PK data suggest that some high-risk individuals may get inadequate protection from every 4 week dosing. Future research should explore this gap in knowledge and PK differences between different populations to inform future dosing schedules.